Surgical treatment of gastric cancer liver metastases: Systematic review and meta-analysis of long-term outcomes and prognostic factors. (July 2021) - Granieri, Stefano; Altomare, Michele; Bruno, Federica; Paleino, Sissi; Bonomi, Alessandro; Germini, Alessandro; Facciorusso, Antonio; Fagnani, Daniele; Bovo, Giorgio; Cotsoglou, Christian
Graphical abstract: Highlights: The prognosis of patients with metastatic gastric cancer is poor. Currently the standard of care for these patients remains palliative treatment. Surgical resection of liver only metastases can lead to favorable outcomes. Patients undergoing surgical resection for gastric cancer liver metastases need to be carefully selected. Abstract: The prognosis of patients with metastatic gastric cancer remains dismal, with palliative treatment as standard of care. However, encouraging results have been reported for surgical resection of liver only metastatic gastric cancer in carefully selected patients. A systematic review of articles published from 2000 onwards was conducted according to PRISMA guidelines. Twenty-nine studies were included in qualitative and quantitative analysis. Meta-analysis of proportions pointed out 29.1 % 5ySR (I 2 = 39 %). The pooled weighted median of MSTs was 31.1 months. T stage > 2, metastasis greatest dimension ≥ 5 cm, the presence of multiple metastases and bilobar disease resulted among the strongest predictors of mortality. Funnel plots, Egger's tests, and P-curve analyses failed to show significant publication bias. Based on strict selection criteria and robust statistical analyses, our results show that, in very carefully selected patients without extrahepatic disease, surgical resection with curative intent may significantly improve overall survival.